2012
DOI: 10.1177/1094670511435563
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Role of Stress in Evaluating Negative Services

Abstract: Since negative services are usually sought during emergencies or when problems arise or to ensure against unwanted outcomes, they are typically accompanied by high levels of stress. Our study investigates the role of stress in evaluating such services. We examine citizen satisfaction with a specific negative service, police services, and the moderating role of stress in the evaluation of these services. Findings from our study confirm the moderating role of stress in satisfaction with police services, which de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 58 publications
1
19
0
1
Order By: Relevance
“…The qualitative study focused on emotionally charged service encounters because they are more likely to (1) elicit specific emotional needs of customers that require the attention of employees (Price, Arnould, and Deibler 1995;Singh and Duque 2012), (2) be memorable for the customer (Baumeister et al 2001;Price, Arnould, and Tierney 1995), and (3) influence important outcomes such as overall satisfaction (Grace 2007) and word-of-mouth communication (Rimé 2009). In addition, if something goes wrong during an emotionally charged service encounter, the customer often pays considerable attention to the employee and the service process (i.e., how the employee handles the situation and responds; Parasuraman 2010).…”
Section: Stage 1: Specifying the Construct Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…The qualitative study focused on emotionally charged service encounters because they are more likely to (1) elicit specific emotional needs of customers that require the attention of employees (Price, Arnould, and Deibler 1995;Singh and Duque 2012), (2) be memorable for the customer (Baumeister et al 2001;Price, Arnould, and Tierney 1995), and (3) influence important outcomes such as overall satisfaction (Grace 2007) and word-of-mouth communication (Rimé 2009). In addition, if something goes wrong during an emotionally charged service encounter, the customer often pays considerable attention to the employee and the service process (i.e., how the employee handles the situation and responds; Parasuraman 2010).…”
Section: Stage 1: Specifying the Construct Domainmentioning
confidence: 99%
“…In emotionally charged service encounters, customers expect employees to address their emotional needs (Menon and Dubé 2000;Singh and Duque 2012). Employees' competence in responding to customers' emotions thus can affect customer evaluations and behavioral intentions (Bagozzi, Gopinath, and Nyer 1999;Menon and Dubé 2000).…”
mentioning
confidence: 99%
“…Stress is a highly complex process (e.g., chronic versus temporary stress) and not captured easily (e.g., McEwen et al, 2015). While previous research has focused on the impact of self-reported stress levels (Singh and Duque, 2012), neurophysiological tools (e.g., galvanic skin response, cardiovascular measures) and biochemical tools (e.g., measure cortisol levels) are well suited to measure different aspects of stress objectively (Föhr et al, 2015;Goyal et al, 2016;Seemann et al, 2016).…”
Section: Future Research Opportunities Related To Internal Cuesmentioning
confidence: 99%
“…For example in a study conducted by Khorshidifer and Abidi [59] stress, itself, has been studied as a moderating variable between locus of control and job satisfaction / performance. As in [60], the moderating role of stress was analyzed in evaluating negative services. Moreover as in [61], the moderating role of stress has been analyzed between one of the personality type named neuroticism and marital violence.…”
Section: ) Software Engineering Occupational Stressmentioning
confidence: 99%